2007
DOI: 10.1063/1.2753587
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions and corresponding magnetic entropy changes in Ni2Mn0.75Cu0.25−xCoxGa Heusler alloys

Abstract: Articles you may be interested inLarge reversible entropy change at the inverse magnetocaloric effect in Ni-Co-Mn-Ga-In magnetic shape memory alloys Detailed studies of room temperature crystal structures, phase transitions, and related magnetic entropy changes ͑⌬S m ͒ in shape memory alloys Ni 2 Mn 0.75 Cu 0.25−x Co x Ga ͑x = 0.0, 0.01, 0.02, 0.025 0.03, 0.05͒ have been carried out by x-ray diffraction, magnetization, and thermal expansion measurements in magnetic fields of up to 5 T and in a temperature inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Being magnetic, these materials can show a strong coupling between structural and magnetic transitions [2][3][4][5][6][7][8]11 which is very appealing for a wealth of different technological applications. In fact, Heusler alloys have been studied quite extensively for their magneto-caloric [13][14][15][16][17] and magnetomechanical [9][10][11][12]18 properties and more recently for their applications in energy conversion 19 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Being magnetic, these materials can show a strong coupling between structural and magnetic transitions [2][3][4][5][6][7][8]11 which is very appealing for a wealth of different technological applications. In fact, Heusler alloys have been studied quite extensively for their magneto-caloric [13][14][15][16][17] and magnetomechanical [9][10][11][12]18 properties and more recently for their applications in energy conversion 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Heusler alloys have been studied 1 Present address: Leibniz Institute of Solid State and Materials Research, Dresden, Germany. quite extensively for their magneto-caloric [13][14][15][16][17] and magneto-mechanical [9][10][11][12]18] properties and more recently for their applications in energy conversion [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coexistence of T M and T C results in a single magnetocrystalline phase transition where a giant magnetic entropy change is observed [12]. Most studies are carried out on the ternary Ni-Mn-Ga alloys and recently the amount of research on the quaternary Ni-Mn-Gabased alloys has grown [13][14][15][16][17][18]. The substitution of Mn by Fe in Ni 2 MnGa-based compounds causes a decrease of T M and an increase of T C [14].…”
Section: Introductionmentioning
confidence: 96%
“…[18][19][20][21][22] The earliest systematic study of Cu-containing NiMnGa showed that addition of Cu on Ni site rapidly suppresses martensitic transformation in Ni 2Àx Cu x MnGa which disappears for the x ¼ 0.1 composition. 23 When nominal content of Ni is kept stoichiometric in Ni 2 MnGa, the addition of Cu to this ternary Heusler compound allows one to smoothly adjust both magnetic and structural transition temperatures [24][25][26] or brings about an uncommon transformation sequence from low-temperature non-magnetic martensite to high-temperature ferromagnetic austenite.…”
Section: Introductionmentioning
confidence: 99%